Respuesta del melón cucumis melo l híbrido edisto sometido a densidades y aplicación de bioestimulantes - Abad Burgos, Wilmer Stalin (2010)
The present investigation work was carried out in the Property "San Vicente", located in the place the plum tree, to 3 km of the parish Palmales of the canton Sands county of The Gold that is located in the geographical coordinates is: latitude 03º 33' S, longitude 80º 06' W and an altitude of 15 msnm, in which a tropical thorny mount is presented (I-T). The objectives outlined in the same one are: 1. to determine the best density in siembra of the hybrid Edisto; 2. to measure the answer from the Hybrid Edisto to the bioestimulantes application; and 3 to analyze the profitability of the different treatments in study . The factors that were studied were siembra densities (factor TO: 12 500, 16 600 and 25 000 plants for hectare) and bioestimulantes application (factor B: witness, oligosacáridos, complex and sour regulator Giberélico), of where to the interaccionar this factors twelve combinations were obtained and they were carried out four repetitions, giving 48 units experimentables as a result. The variables that were evaluated are pointed out: Number of alive plants to the siembra, days to the floración, fructification and it harvests, number of harvested fruits, longitude, diameter and weight of the fruit, plants to the crop, harvested fruits, fruits category TO, B and C, drawers category TO, B and commercial and economic analysis. In the rehearsal a statistical model of Blocks was used at random with factorial arrangement 3x4, and the comparison of classes by means of the test of Tukey that was supplemented with the analysis of the index numbers, the obtained data they were processed by means of the on-line statistical program MINITAB 15. The siembra distance that he/she obtained better vouchers in the evaluated variables was the A3 (25 000 plants for hectare), while in the bioestimulantes use the use of the factor B1 (oligosacáridos) he/she had better values. The interaction of the studied factors was quantified in a significant way for the variable days to the floración, fructification, harvests, number of harvested fruits, longitude, diameter and weight of the fruit, plants to the crop, harvested fruits. The oligosacáridos applied as bioestimulantes marked a difference on the other ones, since of the studied treatments the one that obtained the best results was the A3B1 (25 000 plants for hectare and oligosacáridos application) that presented a net utility of $. 8 314,37 corresponding to a relationship B/C (costo/beneficio) of 1,21 with a profitability of 121,00%.